2024
DOI: 10.1007/s10456-024-09911-1
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in retinal angiogenesis and diabetic retinopathy

Aiyan Hu,
Mirko H. H. Schmidt,
Nora Heinig

Abstract: Diabetic retinopathy has a high probability of causing visual impairment or blindness throughout the disease progression and is characterized by the growth of new blood vessels in the retina at an advanced, proliferative stage. Microglia are a resident immune population in the central nervous system, known to play a crucial role in regulating retinal angiogenesis in both physiological and pathological conditions, including diabetic retinopathy. Physiologically, they are located close to blood vessels and are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 157 publications
0
0
0
Order By: Relevance
“…In DR, microglia alter ligand expression patterns or secrete angiogenic factors to influence pathogenic angiogenesis and ECs can alter the microglia phenotype in turn. 78 Ben et al. 50 deployed a set of ligand–receptor paired interactions in STZ‐induced diabetic and control mice and found that the diabetes‐induced Csf1r‒Csf1 was significantly enriched in microglia and ECs.…”
Section: Cell‒cell Communication In Drmentioning
confidence: 99%
See 2 more Smart Citations
“…In DR, microglia alter ligand expression patterns or secrete angiogenic factors to influence pathogenic angiogenesis and ECs can alter the microglia phenotype in turn. 78 Ben et al. 50 deployed a set of ligand–receptor paired interactions in STZ‐induced diabetic and control mice and found that the diabetes‐induced Csf1r‒Csf1 was significantly enriched in microglia and ECs.…”
Section: Cell‒cell Communication In Drmentioning
confidence: 99%
“…In addition to inflammation, the activation and accumulation of microglia are also correlated with pathogenic angiogenesis in DR. 75,78 Although studies using OIR models have reported a switch from M1 polarised microglia in the early stage of neovascularisation towards M2 polarisa-tion in the late phase, 79 the specific phenotype of microglia exerting promotional or inhibitory effects is relatively unclear. He et al 51 performed single-cell RNA profiling on the retinal microglia of OIR mice and identified a subpopulation that highly expressed the necroptosis-related genes Rip3 and Mlkl.…”
Section: Microgliamentioning
confidence: 99%
See 1 more Smart Citation